Urgensitas Career Development Center Pada Perguruan Tinggi: Studi Literatur Review - Ilahi, Fauzi Nur; Novitasari, Novitasari (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2025)
Abstract: The study of career guidance programs is currently being widely discussed, especially career guidance programs at the college level, one of the reasons is because career planning is an important aspect in supporting the future. Career guidance is a process of helping individuals understand themselves and providing an overview of the world of work, with the ultimate goal that individuals are expected to be able to adjust to the world of work. This study aims to provide an overview of the importance of career guidance programs at the college level. This study uses a literature review method, where data collection uses journal literature sources and other related sources. The results of this study illustrate that career development programs in colleges are important to implement.